2009
DOI: 10.1002/pssa.200880784
|View full text |Cite
|
Sign up to set email alerts
|

High‐performance UV emitter grown on high‐crystalline‐quality AlGaN underlying layer

Abstract: Al0.25Ga0.75N films were grown on a grooved‐Al0.25Ga0.75N/ AlN/sapphire template by MOVPE. The dislocation density on the grooved areas was as low as 1 × 108 cm–2. We fabricated a UVA light‐emitting diode grown on such an AlGaN underlying layer exhibiting an output power of 12 mW at a DC current of 50 mA with a peak emission wavelength of 345 nm, which corresponds to an external quantum efficiency of 6.7%. This efficiency is the highest reported to date in this wavelength region. We also fabricated a 358 nm UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 13 publications
0
43
0
Order By: Relevance
“…Previously, we reported that the crystalline quality of AlGaN on AlN was much improved by growing AlN on a grooved AlN template [1]. The highest efficiency UV LEDs [2] and also UV laser diodes (UV LDs) [3] can be successfully fabricated using a grooved AlN template. However, this grooved template technology requires an additional etching process, which reduces the yield of the devices and increases the process cost.…”
Section: Introductionmentioning
confidence: 98%
“…Previously, we reported that the crystalline quality of AlGaN on AlN was much improved by growing AlN on a grooved AlN template [1]. The highest efficiency UV LEDs [2] and also UV laser diodes (UV LDs) [3] can be successfully fabricated using a grooved AlN template. However, this grooved template technology requires an additional etching process, which reduces the yield of the devices and increases the process cost.…”
Section: Introductionmentioning
confidence: 98%
“…The growth temperature was over 1000 o C for AlGaN layers and up to 1400 o C for AlN. The growth pressure was 6.6×10 4 Pa. During the Al 0.25 Ga 0.75 N growth, 30 μmol/min TMGa, 13 μmol/min TMAl, and 60 μmol/min ammonia were typically injected into the MOVPE reactor. Ridge stripe laser structures were processed from the above two wafers.…”
Section: Methodsmentioning
confidence: 99%
“…We have reported UV LDs on grooved AlGaN templates prepared by heteroepitaxial lateral overgrowth (ELO) [6] and/or hetero-facet-controlled ELO [7]. In this paper, we report two issues related to these UV LD structures.…”
Section: CMmentioning
confidence: 96%
See 2 more Smart Citations